The Effect of Rainfall and Rain Days On Palm Oil Production - Wandha Atmaka Aji; Subakho Aryo Saloko; Indra Kurniawan; Mukti Ahmad Nurcahya (Akademi Komunitas Perkebunan Yogyakarta, 2022)
One of the determining factors for water availability for palm oil plants that do not use irrigation systems is rainfall. The availability of water is a major factor that limits the level of production of palm oil plants. The availability of water for oil palm plants in the field is obtained from rainfall data. This research was conducted at PT. Menthobi Makmur Lestari, Lamandau Regency, Central Kalimantan Province, from June 2021 to July 2021. This study uses secondary data analysis including data on of fresh fruit bunches (TBS) production components in the form of components of the number of fruit bunchesg, average fruit bunches weight, number of productive principals, seed fruit bunches weight; data on the production of fres TBS; rainfall data; and monthly rainy day data in 2017, 2018 and 2019 in 6 Divisions. The results of the analysis showed that variable rainfall and rainy days had a real effect on the increase in TBS production at the age of 5 years. Correlation results in plants aged 12, 15 and 18 years with a two-way analysis at the test level of 1% showed the variable rainfall and rainy day had a strong, real and unidirectional relationship. The correlation value of rainfall and consecutive rainy days is 0.892; 0,887; and 0.855 with significance value of 0.000.